2021
DOI: 10.1101/2021.02.08.21251352
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Post SARS CoV 2 Fatigue among Physicians Working in COVID Designated Hospitals in Dhaka, Bangladesh

Abstract: Background: Fatigue has been observed after a number of infectious disease outbreaks around the world. After the outbreak of SARS CoV-2 in Wuhan, China in 2019, the disease turned into a pandemic very rapidly. Mental health is a key issue associated with such outbreaks. To explore the fatigue level among physicians working in designated public and private hospitals in Bangladesh, we conducted a matched case-control study of post-SARS-CoV-2 fatigue. Method: In this study 105 physicians who were diagnosed as C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
0
2
1
Order By: Relevance
“…Locally, in a study conducted among physicians at Dhaka Medical College Hospital, fatigue level was found to be higher among SARS-CoV-2 infected individuals compared to control group. But, interestingly, no association could be established between fatigue and pre-existing co-morbidities, which are in stark contrast to our findings (Hasan et al, 2020). Another study conducted at same institution among post-COVID patients after one month, found 70% of study participants to be suffering from some form of fatigue (Mahmud et al, 2021).…”
Section: Discussioncontrasting
confidence: 99%
“…Locally, in a study conducted among physicians at Dhaka Medical College Hospital, fatigue level was found to be higher among SARS-CoV-2 infected individuals compared to control group. But, interestingly, no association could be established between fatigue and pre-existing co-morbidities, which are in stark contrast to our findings (Hasan et al, 2020). Another study conducted at same institution among post-COVID patients after one month, found 70% of study participants to be suffering from some form of fatigue (Mahmud et al, 2021).…”
Section: Discussioncontrasting
confidence: 99%
“…individuals compared to control group. But, interestingly, no association could be established between fatigue and pre-existing co-morbidities, which are in stark contrast to our findings(Hasan et al, 2020). Another study conducted at same institution among post-COVID patients after one month, found 70% of study participants to be suffering from some form of fatigue(Mahmud et al, 2021).…”
contrasting
confidence: 99%
“…A fadiga é um dos sintomas mais comuns em pacientes com COVID-19 14 . Além de estar presente nos quadros vigentes da infecção, alguns estudos demonstraram que seu desenvolvimento pode continuar em uma síndrome de fadiga pós-viral 15,16 , sendo demonstrada em estudo brasileiro, em que 57,2% (n=584) da amostra apresentaram persistência da fadiga pós COVID 14 .…”
Section: Discussionunclassified